An Assessment of Recent Initiatives for Financial Inclusion with Reference to Social Security Motto Jan Dhan to Jan Suraksha in India - Mahesh Yadav (International Journal of Rural and Regional Development, 2024)
This research paper aims at assessing the recent initiatives by the Government of India with reference to the financial inclusion of common people in India. Financial freedom is one of the agents of economic growth of a country. Looking at the enormous amount of opportunities towards economic development in India, financial inclusion of people becomes necessary. Financial inclusion has been a matter of wide discussion amongst the policymakers and the Governments. India has been struggling with the poverty, especially in rural areas, having majority of these poor in villages. The Government has been implementing different schemes and programmes to empower rural and unprivileged population. Various schemes have been implemented for the purpose of strengthening financial services and financial inclusion. The National Mission for Financial Inclusion(NMFI) was initiated by the Government of India which is also known as Pradhan Mantry Jan-Dhan Yojana (PMDJY) aiming “Jan-Dhan to Jan Surahsha” This paper aims to examine of “Jan Dhan to Jan Suraksha” programmes and to identify problems of the programmes.
Keywords: Financial Inclusion; financial services; social security